IN TEACHING READING COMPREHENSION TO SECONDARY EDUCATION LEVEL STUDENTS - Ardayati Ardayati; Herlensi Zesti (Universitas Negeri Padang, 2018)
The Objective of this research was to find out whether or not it was significantly effective after applying Concept Oriented Reading Instruction (CORI) Strategy in teaching reading comprehension to secondary education level students. The subject of this research was eighth grade students of SMP Negeri 13 Lubuklinggau. This strategy was applied by using pre-experimental method with one group pretest-posttest design. The total population was 110 students and sample of the research was 28 students. The data was collected through test in the form of multiple choice which consisted of 25 test items. The data was analyzed by using four techniques : 1) Students’ individual score, 2) Minimum mastery criteria, 3) Normality testing and 4) Pairedt-test calculation. The result of the research showed that students’ mean score in the pre-test was 64.00 while students’ mean score in the post-test was 76.00. Finally, the result of paired t-test was 11.43 which was higher than 1.703. It showed clearly that the null hypotheses (Ho) was rejected and the alternative hypotheses (Ha) was accepted. It can be concluded that Concept Oriented Reading Instruction (CORI) Strategy was effective in teaching reading comprehension to secondary education level students at SMP Negeri 13 Lubuklinggau.